Provision of ecosystem services in the lagoon of Venice (Italy): an initial spatial assessment - Rova, Silvia; Pranovi, Fabio; Müller, Felix (Ecohydrology & Hydrobiology, 2015)
The lagoon of Venice is a complex human–environmental system where several environmental, economic and social issues call for new integrated management perspectives. The ecosystem services approach can provide a new framework for the management of this area, and one of the first steps towards its application is ecosystem services mapping. In this work, the spatial distribution of ecosystem services in the lagoon of Venice was assessed in a qualitative way. Seven ecosystem services were chosen for the assessment: four provisioning services (aquaculture, fish and seafood, wild food and crops), two cultural services (recreation and tourism and knowledge systems) and one regulating service (erosion regulation). The services were mapped by integrating biophysical and socio-economic information, resulting in an easily understandable representation of the services provided. The ecosystem services maps were used to perform a zonal analysis, referred to the water bodies adopted in compliance with the Water Framework Directive, which allowed to identify the patterns of ecosystem services provision that characterize each water body.